4.1k views
5 votes
Tony solves the linear equation 3(x - 3) + 2x + 9 = 2x + 2(x - 1) using the step shown below.

Step 1: 3x - 3 + 2x + 9 = 2x + 2x - 1
Step 2: 5x + 6 = 4x - 1
Step 3: 5x - 4x = -1 - 6
Step 4: x = -7
a. He incorrectly combined like terms.
b He incorrectly applied the addition and subtraction properties of equality.
c He incorrectly applied the multiplication and division properties of equality.
d He distributed incorrectly.

User Ataulm
by
4.9k points

1 Answer

3 votes

Answer:

D.)

Explanation:

because when you have numbers inside the parentheses, you have to multiply both of those numbers by the number to the right of the parentheses, not just the X.

User Tim Rutter
by
5.6k points